2006
DOI: 10.1111/j.1365-2621.2006.tb12407.x
|View full text |Cite
|
Sign up to set email alerts
|

Browning Inhibition in Fresh‐cut‘Fuji’Apple Slices by Natural Antibrowning Agents

Abstract: ABSTRA ABSTRA ABSTRA ABSTRA ABSTRACT CT CT CT CT: R : R : R : R : Response sur esponse sur esponse sur esponse sur esponse surface methodology was used to study the effect of antibr face methodology was used to study the effect of antibr face methodology was used to study the effect of antibr face methodology was used to study the effect of antibr face methodology was used to study the effect of antibro o o o owning agents (4-hexylr wning agents (4-hexylr wning agents (4-hexylr wning agents (4-hexylr wning age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
84
0
7

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(101 citation statements)
references
References 28 publications
8
84
0
7
Order By: Relevance
“…Especially in the latter, there is a continuously growing interest in minimally processed fruit because of their convenience and fresh-like quality [1]. This trend has led to research on the development and application of new, safe and effective processing techniques for preserving fresh-cut fruits and vegetables.…”
Section: Introductionmentioning
confidence: 99%
“…Especially in the latter, there is a continuously growing interest in minimally processed fruit because of their convenience and fresh-like quality [1]. This trend has led to research on the development and application of new, safe and effective processing techniques for preserving fresh-cut fruits and vegetables.…”
Section: Introductionmentioning
confidence: 99%
“…As is well accepted, edible films/coatings may serve as carriers of food additives, such as anti-browning agents, antimicrobials, colorants, flavors, nutrients and spices [24]. Some authors [114,120] proved that the coatings were also good carriers for antioxidant agents, such as cysteine, glutathione and ascorbic and citric acids; thus, the addition of LAB to obtain functional edible films and coatings could have successful implications. Several studies were already conducted on different fruits, as is shown in Table 3.…”
Section: Biopreservation and The Use Of Probiotic Coatingsmentioning
confidence: 99%
“…Ascorbic acid also acts as an oxygen scavenger, removing molecular oxygen in polyphenol oxidase reactions. Polyphenol oxidase inhibition by ascorbic acid has been attributed to the reduction of enzymatically formed o-quinones to their precursor diphenols (Özoglu and Bayindirli, 2002;Rojas-Graü et al, 2006;Rico et al, 2007;Jeong et al, 2008).…”
Section: Introductionmentioning
confidence: 99%